Gamification as twenty-first-century ideology. Issue 2 (1st June 2014) - Fuchs, Mathias
Gamification as the process of turning extra-ludic activities into play can be seen in two different ways: following Bataille, we would hope that play could be a flight line from the servitude of the capital-labour relationship. Following Adorno and Benjamin, however, we might discover that the escape from the drudgery of the worker leads to an equally alienating drudgery of the player. I argue that gamification might be seen as a form of ideology and therefore a mechanism of the dominant class to set agenda and to legitimize actions taken by this very class or group. Ever since the notion of gamification was introduced widely, scholars have suggested that work might be seen as a sort of leisure activity. This article analyses the controversial dialectics of play and labour and the ubiquitous notion of gamification as ideology.